Synthesis of 4-aryltetrahydroisoquinolines: Application to the synthesis of cherylline - Somsak Ruchirawat (2018)
A concise route for the synthesis of 4-aryltetrahydroisoquinolines was developed using the addition of Grignard reagents to nitrostyrene derivatives as the key step. The application to the synthesis of cherylline was described.